Superior Gluteal Artery Pseudoaneurysm Caused by Pelvic C-Clamp Blind Application: A Case Report - Kim, Weon-Yoo (Hip Pelvis, 2017)
To control such a hemorrhage, a displaced pelvic ring must be rapidly reduced and stabilized with a pelvic binder, an external fixator, or a pelvic clamp. Among them, pelvic clamps can be life-saving but pin malposition may cause vascular complications. We present a case of superior gluteal artery pseudoaneurysm caused by AO pelvic C-clamp pin malposition.